2022
DOI: 10.3390/nu14102070
|View full text |Cite
|
Sign up to set email alerts
|

Current Hydration Habits: The Disregarded Factor for the Development of Renal and Cardiometabolic Diseases

Abstract: Improper hydration habits are commonly disregarded as a risk factor for the development of chronic diseases. Consuming an intake of water below recommendations (underhydration) in addition to the substitution of sugar-sweetened beverages (SSB) for water are habits deeply ingrained in several countries. This behavior is due to voluntary and involuntary dehydration; and because young children are exposed to SSB, the preference for a sweet taste is profoundly implanted in the brain. Underhydration and SSB intake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 119 publications
(146 reference statements)
1
3
0
Order By: Relevance
“…Our data are consistent with previous reports from epidemiological and interventional studies that link hypohydration biomarkers including higher serum sodium and copeptin as well as low fluid intake with adverse health effects and increased risk of mortality. 38 , 39 , 40 , 41 , 42 , 43 , 44 In agreement with the ARIC data from four U.S. communities that were used in current study, similar sodium levels, >144 mmol/l, were found to be associated with increased risk of all-cause and chronic disease associated mortality within 3–6 years for U.S. adults aged 51–70 years in 2009–2012 National Health and Nutrition Examination Survey (NHANES). 45 Owing to long 25 years follow-up period, our analysis demonstrated that serum sodium is able to predict faster rate of the biological aging and increased risk of future development of chronic diseases well before the age at which the chronic diseases start appearing at high rate in general population.…”
Section: Discussionsupporting
confidence: 85%
“…Our data are consistent with previous reports from epidemiological and interventional studies that link hypohydration biomarkers including higher serum sodium and copeptin as well as low fluid intake with adverse health effects and increased risk of mortality. 38 , 39 , 40 , 41 , 42 , 43 , 44 In agreement with the ARIC data from four U.S. communities that were used in current study, similar sodium levels, >144 mmol/l, were found to be associated with increased risk of all-cause and chronic disease associated mortality within 3–6 years for U.S. adults aged 51–70 years in 2009–2012 National Health and Nutrition Examination Survey (NHANES). 45 Owing to long 25 years follow-up period, our analysis demonstrated that serum sodium is able to predict faster rate of the biological aging and increased risk of future development of chronic diseases well before the age at which the chronic diseases start appearing at high rate in general population.…”
Section: Discussionsupporting
confidence: 85%
“…Vasopressin, as a major regulator of water homeostasis within the body, also plays an important role in glucose homeostasis. Inadequate water intake induces elevated levels of vasopressin, which stimulates vasopressin V1b receptors on the pancreatic islets, thereby causing increased levels of glucagon and adrenocorticotropic hormone, and thus ultimately leading to diabetes [ 23 , 49 ]. Moreover, current evidence from the population and experiment indicated that high plasma copeptin concentrations, a surrogate marker of vasopressin, were associated with increased risk of type 2 diabetes, which also suggested another potential link between poorer hydration status and diabetes [ 24 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proper hydration is important to prevent the development of diabetes, as it is essential in blood glucose regulation [ 22 ]. Current biological evidence suggests that inadequate hydration status increases vasopressin (AVP) levels, thereby mediating organs such as the pancreatic islets, liver, and hypothalamus and causing imbalances in blood glucose levels, which affects the metabolic system and ultimately leads to diabetes [ 23 ]. With hydration status gaining attention, several observational studies have found significant associations between markers of dehydration and increased risk of diabetes [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…One way to assess hydration status is to look for signs of underhydration, in which patients tend to show elevations in urine osmolality (>500 mOsm/l), mild hypernatraemia or elevations in plasma copeptin (a biomarker for vasopressin) [ 18 , 19 ]. For the CKD patient, serum sodium may be a better measurement than urine osmolality since the latter may be affected by medications [sodium–glucose co-transporter-2 (SGLT2) inhibitors, diuretics and lithium] or impaired urinary concentration from diabetes or CKD.…”
Section: Clinical Tips For the Management Of Patients With Ckd At Ris...mentioning
confidence: 99%